Choosing the Right Protocol to Establish MCF-7 Tumor Xenograft in Nude Mice - Behzadi, Ramezan; Ahmadpour, Sajjad; Amiri, Fereshteh T.; Kavosian, Saeid; Asori, Mohsen; Hosseinimehr, Seyed Jalal (Anti-Cancer Agents in Medicinal Chemistry, 2023)
Background: Xenografts of various human cancers in nude mice provide a helpful model in cancer research. This study aimed to develop a xenograft mouse model of MCF-7 breast cancer using injectable estradiol valerate. Methods: Thirty healthy female C57 nu/nu mice were engrafted with three protocols to establish an MCF-7 tumor. Injectable estradiol valerate (10 mg/ml) was used as a substitute for estradiol pellets. The development of tumors was recorded daily, and data were statistically analyzed. Histology of bladder, kidney, and tumors was used to estimate tumor establishment and probable urinary adverse effects. Results: According to the findings, the duration of MCF-7 tumor growth was the lowest for protocol B (tumor tissue). Also, this protocol had the highest xenograft yield within the shortest time duration (37 days for protocol B vs. 73 days for protocol A) without causing urinary adverse effects. Conclusion: Our findings revealed that estradiol valerate, which is way less expensive than estradiol pellets, can be used as a tumor proliferator to establish MCF-7 tumors with the highest yield when MCF-7 tumors have been used for xenograft.
Keywords: urinary adverse effects